How to quantify microparticles in RBCs? A validated flow cytometry method allows the detection of an increase in microparticles during storage. Issue 3 (5th February 2017) - Gamonet, Clémentine; Mourey, Guillaume; Aupet, Sophie; Biichle, Sabéha; Petitjean, Régis; Vidal, Chrystelle; Pugin, Aurore; Naegelen, Christian; Tiberghien, Pierre; Morel, Pascal; Angelot‐Delettre, Fanny; Seilles, Estelle; et al.
Abstract : BACKGROUND: The procoagulant and proinflammatory microparticles (MPs) released during storage of packed red blood cells (pRBCs) can potentially modify transfusion benefits. A robust method to quantify MPs in pRBCs is needed to evaluate their impact in clinical trials. STUDY DESIGN AND METHODS: The objective was to validate the preanalytic conditions required to prepare pRBC supernatant as well as a method to quantify and evaluate MP variations over 42 days of pRBC storage.A flow cytometry method with size‐calibrated beads was developed and fully validated. Quantification of MPs in pRBCs (n = 109) was assessed during short‐term (7 days) and long‐term (42 days) storage at 4°C, during short‐term storage (8 hours) at room temperature, and after 2 years frozen. RESULTS: Repeatability, reproducibility, and linearity of the quantification method were validated, and variations during conservation are presented. There was high variability in RBC (erythrocyte) MP (ERMP) and platelet MP (PMP) levels between RBC units, depending on the filter used for leukocyte reduction. During the 42 days of storage at 4°C, significant increases in ERMPs and PMPs occurred (from 58 to 138 ERMPs/µL from Day 2 to Day 42; p = 0.0002; and from 326 to 771 PMPs/µL from Day 2 to Day 42; p = 0.00026). CONCLUSION: We use a robust method to confirm that ERMPs and PMPs are present to various degrees in pRBCs and that storage for 42 days significantly increases their generation. This method is robust enough to allow MP quantification in pRBCs and is adapted to evaluate the clinical impact of transfused MPs in prospective clinical trials.